Emerging Engineering Approaches and Applications - Elwin Mao; Lin Li Xu (Trans Tech Publications Ltd, 2011)
Selected, peer reviewed papers from the 2011 International Conference on Information Engineering for Mechanics and Materials (ICIMM 2011), August 13-14, 2011, Shanghai, China